Spatial learning and memory of young and aging rats following injection with human Wharton’s jelly‐mesenchymal stem cells - Berry Juliandi; Wildan Mubarok; Dian Anggraini; Arief Boediono; Mawar Subangkit; Indra Bachtiar; Harry Murti; Kelvin Yaprianto; Boenjamin Setiawan (Universitas Gadjah Mada, 2021)
Human Wharton’s jelly‐mesenchymal stem cells (hWJ‐MSC) are an emerging potential source of stem cells derived from the umbilical cord. Previous studies have shown their potential as treatment for traumatic brain injury and Parkinson’s disease. However, no study has yet investigated the effect of hWJ‐MSC injections in countering spatial learning and memory impairment in aging rats. The effect of hWJ‐MSC injection on young rats is also unknown. The objective of this research was to analyze the effect of an hWJ‐MSC injection on spatial learning, memory, density of putative neural progenitor cells (pNPC), and neuronal apoptosis in the dentate gyrus (DG) of young and aging rats. Injection of hWJ‐MSC did not change spatial learning and memory in young rats until two months post‐injection. This might be due to retained pNPC density and neuronal apoptosis in the DG of young rats after injection of hWJ‐MSC. In contrast, injection of hWJ‐MSC promoted both spatial learning and memory in aging rats, a finding that might be attributable to the increased pNPC density and attenuated neuronal apoptosis in DG of aging rats during the two months post‐injection. Our study suggests that a single injection of hWJ‐MSC might be sufficient to promote improvement in long‐term learning and memory in aging rats.